Gastroenteropancreatic neuroendocrine tumors and the NETTER-1 trial - Caplin, Martyn (International journal of endocrine oncology, 2017)
Martyn Caplin speaks to Senior Editor: , Roshaine Wijayatunga. Martyn is a professor of gastroenterology and GI neuroendocrinology at the Neuroendocrine Tumour Unit at the Royal Free London and University College London. He is immediate past-Chairman of the European Neuroendocrine Tumor Society. He is founder and past-Chairman of the UK and Ireland Neuroendocrine Tumor Society as well as NCRI Neuroendocrine Tumor Group. He received a lifetime achievement award in recognition of his clinical leadership and research in the field of NETs. Former clinical lead for 'NHS Evidence' for gastroenterology and liver diseases. He has published over 200 peer review papers, written multiple book chapters and co-authored two books. He regularly lectures both nationally and internationally.